Analisis Penarikan Hutang Dalam Kaitannya Dengan Rentabilitas Pada Pt. Tunas Brothers Di Bandar Lampung - Gunawan GUNAWAN (Jurnal Manajemen dan Bisnis, 2011)
This study aimed to determine whether the effect on earnings drawdown of debt capital in PT. Tunas Brothers in Bandar Lampung. The purpose based on the problems faced by PT. Tunas Brothers earned income in the form of fluctuation and the large amount of foreign capital more than the amount of capital used by the company in the years studied. The hypothesis is. if the level of economic profitability of the company is greater than the amount of the interest rate, the withdrawal will have no impact or a positive impact on earnings, equity research uses quantitative analysis and ratio analysis that include: Profit Margin, Operating Asset Turnover, Economic Profitability, Equity earnings and Qualitative Analysis of theoretical approaches to the relationship between the ratio of Debt Equity. From the analysis carried out can be concluded that in the case of withdrawal of debt, the company still did not consider whether the results to be obtained by pulling the debt will be greater than the amount of interest payable or not, so this will make Equity Profitability levels become unmanageable.